Body sensor networks - Yang, Guang-Zhong (Springer London, 2014)
The last decade has witnessed a rapid surge of interests in new sensing and monitoring devices for wellbeing and healthcare. One key development in this area is wireless, wearable and implantable in vivo monitoring and intervention. A myriad of platforms are now available from both academic institutions and commercial organisations. They permit the management of patients with both acute and chronic symptoms, including diabetes, cardiovascular diseases, treatment of epilepsy and other debilitating neurological disorders. Despite extensive developments in sensing technologies, there are significant research issues related to system integration, sensor miniaturisation, low-power sensor interface, wireless telemetry and signal processing.  In the 2nd edition of this popular and authoritative reference on Body Sensor Networks (BSN), major topics related to the latest technological developments and potential clinical applications are discussed, with contents covering   ·         Biosensor Design, Interfacing and Nanotechnology ·         Wireless Communication and Network Topologies ·         Communication Protocols and Standards ·         Energy Harvesting and Power Delivery ·         Ultra-low Power Bio-inspired Processing ·         Multi-sensor Fusion and Context Aware Sensing ·         Autonomic Sensing ·         Wearable, Ingestible Sensor Integration and Exemplar Applications ·         System Integration and Wireless Sensor Microsystems  The book also provides a comprehensive review of the current wireless sensor development platforms and a step-by-step guide to developing your own BSN applications through the use of BSN development kit. Online supplementary materials and the latest updates are available from http://www.bsn-web.org.